Bawiji Musical Ensemble and its role in preserving the folk heritage of the Quesengq region - Chiey Kamal Saddi (Zanco Journal of Humanity Sciences)
The ability of the Bawaghi Group as a vision to continue and develop its performance and work reflects the efforts exerted by those who raise it to improve the technical level of the band. This confirms the concern of the permanent renewal and development commensurate with the band's ambition to present important historical and historical works inspired by our history in contemporary and modern language, Our positive relationships with this history. The band aimed to preserve the popular folk songs, songs, folk songs, folklore and other things, and to confirm our Kurdish Kurdish identity. This is a historical consideration for our struggles and we assure the world of our right to live freely.